(3OjhGf GHf MLQ GdYSbdGfj (B((3efXhe GdOQQ(B)s - (3CMeO Hf Ydj Hf eMeO Hf MLQ GdTGaYj GdcfGfj GdYSbdGfj, TgGH GdOjf CHh GdaVd, GHf MLQ, J (B852 (3g` s; (3GHf MLQ GdYSbdGfj,J (B852 (3g` s ((3Ydj Hf eMeO Gdbje s)
(3ChdgG (B:s
(3CeG HYO(B: (3MeOkG ddg Ydi EMSGfg abO SFdJ ZjQ eQI Cf CLQO ef efXhej efJNHkG, hCf CaQO ef ebGWjYj eG cGf efgG eQbUkG heWQHG s
(3BNQgG (B:s
(3ef GdebGWjY, hbGd(B: (3GdCQV OGQj EPG eG QCjJ QRbkG gfjkG Ef WGH YjTj HCQV CbeJ ajgG edjG s
(3GdLRA GdChd (B239s
(3GfJNHg GHf MLQ ef OjhGfg GdcHjQ hQJHg Ydi SHYI CfhGY SeGgG GdSHYI GdSjGQI GdfjQGJs
(3Yf fSNI ebQhAg Ydi GdeDda HGdeOQSI GdefchJeQjI HGdbGgQI GdeYRjI SfI (B838(3g` hGSJcJHg EjGgG TeS GdOjf eMeO Hf YKeGf Hf eMeO GHf MdI GdhGYXs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs